2010
DOI: 10.1111/j.1445-5994.2009.02097.x
|View full text |Cite
|
Sign up to set email alerts
|

Reversible posterior encephalopathy syndrome associated with bortezomib

Abstract: Reversible posterior encephalopathy (RPES) is an uncommon neurological syndrome that is being increasingly reported in association with anti-neoplastic therapies. The first case of reversible posterior encephalopathy associated with the proteosome inhibitor bortezomib is described and the reported experience of the occurrence of RPES with other antineoplastic therapies reviewed. Dysregulation of cerebral vasomotor autoregulation is postulated as the underlying pathophysiology in this case of bortezomib associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 16 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…Bortezomib competitively inhibits the ChTL activity of all proteasome forms and induces apoptosis preferentially in neoplastic cells. At the same time, bortezomib exhibits side effects: fatigue and weakness, gastrointestinal disturbances, thrombocytopenia, acute pancreatitis, encephalopathy syndrome [35][36][37]. Besides, under the pressure of the continuous proteasome inhibition, cells switch on adaptive feedback mechanisms to eliminate the lethal attack of proteasome inhibitors [38,39].…”
Section: Changes In the Proteasome Pool In The Development Of Human Pmentioning
confidence: 99%
“…Bortezomib competitively inhibits the ChTL activity of all proteasome forms and induces apoptosis preferentially in neoplastic cells. At the same time, bortezomib exhibits side effects: fatigue and weakness, gastrointestinal disturbances, thrombocytopenia, acute pancreatitis, encephalopathy syndrome [35][36][37]. Besides, under the pressure of the continuous proteasome inhibition, cells switch on adaptive feedback mechanisms to eliminate the lethal attack of proteasome inhibitors [38,39].…”
Section: Changes In the Proteasome Pool In The Development Of Human Pmentioning
confidence: 99%
“…The PI bortezomib (Velcade, PS-341) can induce apoptosis, reverse drug resistance of MM, and also affect their micro-environment by blocking cytokine circuits, angiogenesis and cell adhesions [3]. It has been reported that bortezomib can cause reversible posterior leucoencephalopathy (RPLS), which is commonly caused by hypertensive encephalophathy, immunosuppressants, or chemotherapy [4]. The clinical manifestations of RPLS include seizures, headache, altered mental state and visual loss, which is to some extent similar to our case.…”
Section: Discussionmentioning
confidence: 99%
“…PRES is a rare and potentially harmful complication of multiple myeloma (3,5,6). We herein describe a case involving a presentation typical of PRES, in both clinical and radiological aspects, attributed to bortezomib as the most possible offending agent.…”
Section: Discussionmentioning
confidence: 99%
“…Although PRES has been increasingly identified within the setting of oncology among patients receiving chemotherapy and targeted agents (1, 2), only four cases associated with bortezomib treatment have been reported to date (3,(5)(6)(7). The clinical characteristics, including those of the present case, are outlined in Table. Among these cases, there was a female predominance (80%) and preferential attacks among subjects more than fifty years of age.…”
mentioning
confidence: 94%